DUCTECTASIA OF THE BREAST; AN EXPERIENCE WITH HADFIELD OPERATION (RADICAL EXCISION OF THE SUBAREOLAR DUCT SYSTEM) (Iraqi Journal of Medical Sciences, 2017)
Background: Ductectasia of the breast is a benign condition. It is characterized by dilatation of the mammary ducts, which is often associated with periductal inflammation. Recurrent sepsis is often resistant to non-operative management. Furthermore, it can be very difficult to exclude malignancy.Objective: To evaluate the significance of Hadfield operation (radical excision of major mammary ducts) in treatment of ductectasia and in detecting coexistent early carcinoma of the breast that cannot be visualized by ultrasound and mammography.Methods: A Prospective study in Al-Imamein Al-Kadhimein Medical City for female patients with ductectasia of the breast over the period from April 2007 to April 2015. Ultrasound was done for all patients to prove the diagnosis and to exclude any suspicious mass. Mammography was done for patients above 40 years old. Patients with breast mass diagnosed clinically or by investigations were excluded from the study. Patients were divided into two groups according to the type of treatment; (Group A) patients were treated conservatively by antibiotics and analgesia, and (Group B) patients were treated surgically by radical excision of the major mammary ducts (Hadfield operation). Follow up of all patients for at least one year.Results: Over eight years of the study, the total number was 720 female patients, their age ranges from 21 – 55 years with mean age (33±48 year). Group A includes 614 (85.28%) patients, all of them were still complains of nipple discharge and not cured. Group B includes 106 (14.72%) patients all of them were cured from nipple discharge. One patient in Group B accidentally found to have ductal carcinoma in situ of the breast which was not visualized by preoperative ultrasound or by mammography.Conclusion: Conservative management of ductectasia of the breast does not relief symptoms of nipple discharge, while surgical excision of major mammary ducts relief symptoms of nipple discharge. Co-existence of breast carcinoma in situ (which was not appeared by preoperative ultrasound and mammography of the breast) in specimen of excised mammary ducts is an interested finding.Keywords: Ductectasia of the breast; Hadfield operation; early breast carcinoma Citation: Taqi S. Atiyah. Ductectasia of the breast; an experience with hadfield operation (radical excision of the subareolar duct system). Iraqi JMS. 2017; Vol. 15(1): 20-26. doi: 10.22578/IJMS.15.1.4
Keywords: Ductectasia of the breast Hadfield operation early breast carcinoma